The archaeology of southeastern Native American landscapes of the colonial era - Cobb, Charles R. (Charles Richard), 1956- (American experience in archaeological perspective., 2019)
This volume describes the ways Native American populations accommodated and resisted the encroachment of European powers in southeastern North America from the arrival of Spaniards in the sixteenth century to the first decades of the American Republic. Tracing changes to the region's natural, cultural, social, and political environments, Charles Cobb provides an unprecedented survey of the landscape histories of Indigenous groups across this critically important area and time period.